Fibrinogen, Factor VIII Related Antigen, Antithrombin III and α2-Antiplasmin in Peripheral Arterial Disease - Christe, M; Delley, A; Marbet, G A; Biland, L; Duckert, F (Thrombosis and Haemostasis, 1984)
In 306 subjects, 217 without and 89 with peripheral arterial disease (PAD), VIIIR:Ag and α2-antiplasmin are significantly higher in PAD (p < 0.01). In the PAD negative group the ratio α2-antiplasmin/antithrombin III activity is significantly higher 1.11 ± 0.3 in the patients with an abnormal exercise ECG typical of coronary disease than in normal subjects 1.02 ± 0.2 (p < 0.05). In the PAD positive group antithrombin III concentration is higher in patients with a normal exercise ECG than in patients with abnormal exercise ECG (p < 0.05). The same is true for α2- antiplasmin but not for the antithrombin III activity. Fibrinogen and VIIIR:Ag are higher in patients with a previous myocardial infarction, however, the age is also significantly different as compared to the group without previous myocardial infarction. Disturbance of the cerebral arterial circulation is characterized by an elevation of VIIIR:Ag and of α2-antiplasmin as comapred to the values obtained in patients without this complication. There is a general tendency towards higher α2-antiplasmin values with the extension of the arterial disease.
Keywords: Peripheral arterial disease; VIIIR: Ag; Antithrombin III; α2-Antiplasmin; Cerebral arterial disease; Myocardial infarction